Genetic diagnosis in infertile men with numerical and constitutional sperm abnormalities - GÜNEY, AHMET İLTER; TARCAN, TUFAN (MARY ANN LIEBERT, INC, 2008)
Infertile men having numerical or structural sperm defects may carry several genetic abnormalities (karyotype abnormalities, Y chromosome microdeletions, cystic fibrosis transmembrane conductance regulator (CFTR) gene mutations, androgen receptor gene mutations, and abnormalities seen in sperm cells) leading to this situation. First we aimed to investigate the relationship between the numerical and constitutional (morphological) sperm anomalies and the genetic disorders that can be seen in infertile males. Our other aim was to compare two different kinds of kits that we use for the detection of Y chromosome microdeletions. Sixty-three infertile males [44 non-obstructive azoospermic, 8 severe oligozoospermic, and 11 oligoasthenoteratozoospermic] were investigated in terms of somatic chromosomal constitutions and microdeletions of the Y chromosome. Sperm aneuploidy levels were analyzed by fluorescence in situ hybridization (FISH) in sperm cells obtained from the semen of six OAT patients. Microdeletion and sex chromosome aneuploidy (47, XXY) rates in somatic cells were found to be approximately 3.2% and 4.7%, respectively. Sperm aneuploidy rates were determined as 9%, 22%, and 47% in three patients out of six. Two of these three patients also had high rates of head anomalies in semen samples. High correlation was found between sperm aneuploidy rates and sperm head anomalies. Since the introduction of the assisted reproductive techniques for the treatment of severe male infertility, genetic tests and genetic counseling became very important due to the transmission of genetic abnormalities to the next generation. Thus in a very near future, for a comprehensive male infertility panel, it will be essential to include additional genetic tests, such as CFTR gene mutations, sperm mitochondrial DNA mutations, and androgen receptor gene mutations, besides the conventional chromosomal analyses, Y chromosome microdeletion detection, and sperm-FISH analyses.
Keywords: IN-SITU HYBRIDIZATION; Y-CHROMOSOME; HUMAN SPERMATOZOA; ANEUPLOIDY; MICRODELETIONS; INJECTION; TRANSLOCATION; FREQUENCY; NUCLEI; MALES